Siesta: A theory of freelancing - Maria Saez Marti (University of Zurich, Department of Economics, 2011)
I study the effect of fatigue and innate ability on performance in a model with incomplete contracts, lumpy tasks requiring multiple periods of work and stochastic productivity shocks. I find that increasing ability or reducing fatigue does not lead necessarily to more productive efficiency, since it may exacerbate the incentive for agents take too much on-the-job leisure. In a world with heterogenous agents, the problem may be ameliorated by the introduction of a dual labour market with freelancers (who can take breaks at their discretion) and regular workers (who work on a fixed schedule).
Keywords: D0; D8; D9; M51; M55; 330; breaks; leisure; productivity; freelancing; Arbeitszeitgestaltung; Freizeit; Arbeitsproduktivität; Agentenbasierte Modellierung